1996
DOI: 10.1002/ange.19961081527
|View full text |Cite
|
Sign up to set email alerts
|

Prenylierung von Benzoesäurederivaten, katalysiert durch eine Transferase aus Escherichia‐coli‐Überproduzenten: Verfahrensentwicklung und Substratspezifität

Abstract: Stichworte: Cerverbindungen -Kohlenhydrate Manganverbindungen -Radikalreaktionen [I] a) D. Rouzaud, P. Sinay, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…[132] Naphthazarin (64) may be oxidized to the naphthodiquinone (124) (see Scheme 12) upon treatment with Pb(OAc) 4 , [133] or more effectively, phenyliodonium bis(trifluoroacetate). [140] Highly reactive diquinone (124) has been used for the synthesis of cage compounds, [140] and in a synthesis of cycloshikonin (Section 4.3.3, Scheme 12). [141] Reduction of naphthazarin (64) may be effected with a number of reagents.…”
Section: Chemistry Of Naphthazarinmentioning
confidence: 99%
See 1 more Smart Citation
“…[132] Naphthazarin (64) may be oxidized to the naphthodiquinone (124) (see Scheme 12) upon treatment with Pb(OAc) 4 , [133] or more effectively, phenyliodonium bis(trifluoroacetate). [140] Highly reactive diquinone (124) has been used for the synthesis of cage compounds, [140] and in a synthesis of cycloshikonin (Section 4.3.3, Scheme 12). [141] Reduction of naphthazarin (64) may be effected with a number of reagents.…”
Section: Chemistry Of Naphthazarinmentioning
confidence: 99%
“…[123] Similar enzymes have been identified and characterized in ubiquinone biosynthesis, [114] and the utility of a prenyltransferase, formed by E. coli overproduction, in organic synthesis has been demonstrated. [124] It has also been suggested that the biosynthesis may be inhibited by light through the photodegradation of flavin mononucleotide (FMN), a cofactor that may be required for one or more of the oxidation processes that lead to shikonin. In support of this, the FMN photodegradation product lumiflavin was shown to inhibit shikonin biosynthesis, most likely through disruption of PHB geranyltransferase.…”
mentioning
confidence: 99%
“…[123] ¾hnliche Enzyme sind aus der Ubichinonbiosynthese bekannt, [114] und die Nützlich-keit von Prenyl-Transferasen aus E. coli in der organischen Synthese ist bekannt. [124] Es ist auch vorgeschlagen worden, daû Licht die Biosynthese durch den Photoabbau von Flavinmononucleotid (FMN) hemmt. FMN ist ein Cofaktor, der für einen oder mehrere der zur Shikoninbiosynthese notwendigen Oxidationsschritte notwendig sein kann.…”
Section: Biosynthese Von Alkannin Und Shikoninunclassified